2015
DOI: 10.1021/acs.jnatprod.5b00066
|View full text |Cite
|
Sign up to set email alerts
|

Hypermongones A–J, Rare Methylated Polycyclic Polyprenylated Acylphloroglucinols from the Flowers of Hypericum monogynum

Abstract: Hypermongones A-J (1-10), rare methylated polycyclic polyprenylated acylphloroglucinol derivatives, together with three known simple acylphloroglucinols (11-13) as their plausible biogenetic precursors, were identified from the flowers of Hypericum monogynum. The structures of 1-10 were elucidated by analysis of their 1D and 2D NMR spectroscopic data; the absolute configuration of their polycyclic skeleton was determined by the electronic circular dichroism exciton chirality method and was subsequently confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
(48 reference statements)
4
35
0
Order By: Relevance
“…Our results showed that hypermongone C suppresses the secretion of pro-inflammatory markers TNF-α and IL-6. This is consistent with the anti-inflammatory effect of hypermongone G, which features a similar structure to hypermongone C and demonstrates a significant inhibitory effect on nitric oxide production in LPS-induced RAW264.7 macrophages [30].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results showed that hypermongone C suppresses the secretion of pro-inflammatory markers TNF-α and IL-6. This is consistent with the anti-inflammatory effect of hypermongone G, which features a similar structure to hypermongone C and demonstrates a significant inhibitory effect on nitric oxide production in LPS-induced RAW264.7 macrophages [30].…”
Section: Discussionsupporting
confidence: 85%
“…We identified the compound as a PPAP based on our analysis of 1D and 2D-NMR results, having a furan ring, two isoprenyl groups, tertiary and quaternary methyl, and three carbonyl groups connected to different parts of the structure, which are the key features of this class of compounds. The comparison of NMR chemical shifts and MS data with reported values and known compounds in the literature confirmed our compound as hypermongone C [30]. The heteronuclear single quantum coherence (HSQC) and heteronuclear multiple bond correlation (HMBC) correlations established the bicyclic structure (Figure S1).…”
Section: Resultssupporting
confidence: 75%
“…Two known compounds were identified as hypermongones H and F ( 10 and 11 ) by comparison of their spectroscopic and physical data with those of related literature. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…The examples of epimers possessing the same terminal side chain are common in naturally occurring terpene compounds reported in the literature. [22][23] The known iridals were identified as iritectol B (8), iridobelamal A (9), and isoiridogermanal (10) by NMR analysis and comparison with literature data. 7 The various biological activities of iridals have attracted M A N U S C R I P T…”
Section: Resultsmentioning
confidence: 99%